Pola Komunikasi Orang Tua Terhadap Anak Dalam Seleksi Menonton Televisi di Ngentak Sapen, Catur Tunggal, Depok, Yogyakarta. - Hasan, Haryanto (Jurnal Dakwah dan Komunikasi, 2018)
Currently television as one of the modern communication media that very rapid development. This development certainly has positive and negative effects in accordance with the events broadcast by this media.This research uses qualitative research methods, that is to produce data in the form of written or oral words of the people and behavior to be observed, and phenomenological approach intended to know and understand as well as describe what happened in research place clearly and in detail by collecting as much data as possible about parents' communication to children in television viewing selection and parental barriers in communication with children in NgentakSapen, Catur Tunggal, Depok, Yogyakarta Researchers concluded that the pattern of parent communication with children in the selection of watching television runs well although only some of the parents who realize the magnitude of the influence of television for the development of children, especially in speech and behavior, and communication barriers parents with children is not too difficult, although sometimes children like to be angry, denied when ruled, never understood when advised but anyway obstacles that parents can understand it and find a solution to change the barriers and do not forget always give advice to the attitude of such a child does not happen again.